Parental contributors to children's persistence and school readiness: testing a moderated-mediation model - Prendergast, Sarah, author; MacPhee, David, advisor; Lunkenheimer, Erika, committee member; Stevenson, Cerissa, committee member (Colorado State University. Libraries, 2016)
Parental scaffolding skills were assessed in relation to children’s school readiness with children’s persistence examined as a hypothesized mediator. Additionally, parenting styles (authoritative and authoritarian) were assessed as moderators of the association between parental scaffolding and children’s persistence. School readiness was a latent construct comprised of math and language skills, as well as emotion regulation. In a low-income sample of families from the Early Head Start Research and Evaluation Project (N= 2977), parental scaffolding significantly predicted children’s persistence at 36 months, and school readiness in prekindergarten. Persistence partially mediated the link between parental scaffolding and school readiness. Neither authoritative nor authoritarian parenting style moderated the mediational model. The results indicate that parental scaffolding can promote children’s persistence and later school readiness. The findings and implications from this study provide parents and educators with practical ways to promote school readiness among low-income children.